Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jhn.12851
|View full text |Cite
|
Sign up to set email alerts
|

Commercial growing up milks: usage frequency and associated child and demographic factors across four Asia Pacific countries

Abstract: Child feeding practices are changing across the world, driven by economic development and the commercial introduction of alternate food and fluids for children. The relatively recent introduction of commercial toddler or growing up milks (GUMs) has the potential to contribute significantly to food system and dietary pattern alterations. 1,2 GUMs are milkbased products that are low in protein compared to cow's milk,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The studies also reported 48% of toddlers consumed yoghurt (plain, flavoured and custard), 20% consumed dried fruit, 23% consumed sugar and sugary products and 35% consumed discretionary cereal products daily (based on 24 h recall and food-frequency questionnaires). Additional Australian research reported around 36% of toddlers consume toddler milk daily [ 16 ], and Australian national health survey data has also shown that close to 40% of toddlers aged 2-3 years consume yoghurt daily and close to 50% consume confectionery and cereal/nut/fruit/seed bars daily [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies also reported 48% of toddlers consumed yoghurt (plain, flavoured and custard), 20% consumed dried fruit, 23% consumed sugar and sugary products and 35% consumed discretionary cereal products daily (based on 24 h recall and food-frequency questionnaires). Additional Australian research reported around 36% of toddlers consume toddler milk daily [ 16 ], and Australian national health survey data has also shown that close to 40% of toddlers aged 2-3 years consume yoghurt daily and close to 50% consume confectionery and cereal/nut/fruit/seed bars daily [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a key driver of the obesity epidemic worldwide [ 14 ]. Global research indicates that toddlers are becoming regular consumers of commercially available foods and milks [ 15 , 16 ]. An Australian study found that discretionary foods contributed just over 10% of total energy intake in toddlers [ 15 ], and packaged infant and toddler snack foods made up 9% of this total.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that nutrient content claims are being made on products that overall do not have a suitable sugar profile for this age group and may be misleading some caregivers into believing that these products are nutritionally required for their young child's health and development. Addressing the concerning levels of sugar content in GUMs is particularly important given the burgeoning GUM market and increasing reach of these products into the diets of young children globally (Willcox et al, 2021). Between 2005 and 2019, breast-milk substitute sales volume increased by 122%, but this was primarily driven by GUMs, which grew by over 220% and contributed nearly half of total sales by volume for breast-milk substitutes in 2019 (Baker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As of 2017, nearly three quarters (72.9%) of non-breastfeeding children 6-23 months of age were consuming a breast-milk substitute (National Population and Family Planning Board et al, 2018). A recent health facility-based survey in Bandung City, Indonesia, identified that half of 12-to 35-month-olds had consumed a breast-milk substitute in the previous day (Helen Keller International, 2021), and a survey among mothers living in Jakarta found that GUMs were consumed seven or more times per week by nearly one third of young children 12-35 months of age (Willcox et al, 2021).…”
Section: Introductionmentioning
confidence: 99%